POSSIBLE OTRIVINE-INDUCED BRUTAL BILATERAL EXSUDATIVE RETINAL DETACHMENT - LOUIS DE GONZAGUE, MIRAY (Advances in Social Sciences Research Journal, 2019)
Retinal detachment (RD) is the separation of the neurosensory retina (NSR) from the underlying retinal pigment epithelium (RPE). The purpose is to report a case of patiente presenting a brutal bilateral exsudative retinal detachment. A 25-year-old woman with no significant ocular history noted rapid, painless blurring in both eyes, facial edema and buccal dryness 2 days following a nasal spray of Otrivine by selfmedication for nasal stuffiness . Her best-corrected visual acuity was hand movement perception in both eyes. The anterior chamber, iris, and intraocular pressures were within normal limits. Dilated fundus examination showed clear vitreous with intraretinal hard exsudats mimicking an hypertensive retinopathy and inferior retinal detachment in both eyes. We suspected a drug-induced retinal detachment. We ask several experts for their opinion toward this case. Physicians should enquire about the overuse of nasal sprays.They must monitor patients’ use of nasal sprays containing oxymetazoline and advise those with chronic nasal congestion that the overuse of this drug may be dangerous.